اغتفار الربا التابع غير المقصود بالتعامل في الصكوك المختلطة في ضوء قاعدة التبعية = Forgiveness of Riba in mixed assets Sukuk trading in light of the dependency rule - Awang, Abdul Bari; Md. Sawari, Mohd. Fuad; Burhan Uddin, Mohammad (Faculty of Shariah, Sultanate of Oman, 2021)
The research aims to highlight the issue of forgiveness of usury in mixed assets sukuk trading in the scope of the rule of dependency. The research discusses the meaning of dependency from a Fiqh perspective, then proves the rule of dependency with evidence from the Qur'an, Sunnah, scholarly consensus, analogies and customs, and finally presents the views of contemporary jurists and late scholars on the forgiveness of usury using mixed instruments of underlying assets, usufructs, money, and debts. The research uses on the inductive method by referring to the references of jurisprudence of the four sects and the views of contemporary jurists on the subject. He uses the analytical method through comparing opinions, analyzing evidence and weighing various perspectives. The research concludes that usury in mixed assets sukuk trading of underlying assets, usufructs, money and debts is forgiven matter, based on the legal maxims: “anything subordinate follows” and “the follower does not singly rule”, according to certain regulations and conditions.